The Effect of Bank Funding Sources on Total Revenue and Impact on Profit : Study on Joint Financial Reports of Sharia Banks and Sharia Business Units in Indonesia 2014-2020 - Wiwit Mustafidah (JPSDa: Jurnal Perbankan Syariah Darussalam, 2023)
In general, companies in operations use funds sourced from debt, own capital, or theresults of investment/financing from outside parties. Likewise, Islamic banks in theiroperations also use these sources of funds. Selection of alternative sources of fundsused can affect the level of company profitability as measured by profit. This studyaims to determine whether there is an effect of sources of funds originating from bankdebt (liability banks), securities issued, and bank third party funds on total incomeand the impact on profits of Islamic banks in Indonesia in 2014-2020. This study usesa quantitative approach with the type of case study research by analyzing the combined financial statements of Islamic banks and Islamic business units inIndonesia from 2014-2020 published on the websites of Bank Indonesia and theFinancial Services Authority. The data analysis technique used is Path analysistechnique with variables X1: Bank debt (bank liability), X2: Securities issued, X3:Third party funds, Y: Profit and Z: Total Revenue. The research results show that bankdebt and third party funds have no partial effect on total income, but simultaneouslyhave a significant effect. Debt and securities variables have no effect on profits, whilethird party funds and total income have a significant effect on profits. The variablethat has the greatest influence contribution is the total income variable.